THE EFFECT OF THINK PAIR SHARE STRATEGY ON STUDENTS READING COMPREHENSION ACHIEVEMENT - Khairuni Syafitri; Rafika Dewi Nasution (Universitas Negeri Medan, 2015)
This study was conducted as an attempt to find out the effect of Think Pair Share Strategy on students’ reading comprehension achievement. This research used the experimental design. The population of this research was the students of SMP Budisatrya. The Sample of this research was the 2014/2015 seventh grade students of SMP Budisatrya with the total number 40 of students as sample taken by using random sampling technique. The research was divided into two groups: experimental and control groups. The instrument used to collect the data was multiple choice tests of pre-test and post-test. To obtain the result of the reliability of the test, the Kuder Richardson formula (KR21) was used. The result of the calculation showed that the reliability of the test was significant. The data were analyzed by using t-test formula. The result of the analysis showed that t- value was higher than t- table (2.46>2, 021) at the level of significance 0,05 with the degree of freedom (df) 38. Therefore, null hypothesis (H0) is rejected and hypothesis alternative (Ha) is accepted. It means that there is a significant effect of using Think Pair Share Strategy on students’ reading comprehension achievement.